Exclusion and Counter‐exclusion: The Struggle over Shrimp Farming in a Coastal Village in Bangladesh. Issue 4 (1st June 2017) - Afroz, Sharmin; Cramb, Rob; Grünbühel, Clemens
ABSTRACT: This article explores the processes whereby control over land and water is exercised in the context of commercial shrimp cultivation in coastal Bangladesh. The authors draw on the insight that the exercise of control over resources implies both inclusion for some and exclusion for others, and that shifting the boundary between the two involves the deployment of four interacting 'powers of exclusion' — regulation, the market, force and legitimation — the effectiveness of which depends on specific historical conjunctures. The article uses a case study of a village in Khulna District to explore: (a) the processes by which poor farmers were excluded from their land by large shrimp farmers; (b) the ways in which villagers experienced the changes in land use and social relations associated with the shrimp boom; and (c) the conjunction of internal and external factors that enabled smallholders to collectively mobilize to reverse their exclusion from the land. Understanding these messy and contingent processes of exclusion and counter‐exclusion helps to inform strategies aimed at securing the property rights and livelihoods of the rural poor.